2022
DOI: 10.1186/s13613-022-01051-3
|View full text |Cite
|
Sign up to set email alerts
|

A stratification strategy to predict secondary infection in critical illness-induced immune dysfunction: the REALIST score

Abstract: Background Although multiple individual immune parameters have been demonstrated to predict the occurrence of secondary infection after critical illness, significant questions remain with regards to the selection, timing and clinical utility of such immune monitoring tests. Research question As a sub-study of the REALISM study, the REALIST score was developed as a pragmatic approach to help clinicians better identify and stratify patients at high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 45 publications
(76 reference statements)
1
2
0
Order By: Relevance
“…These results are in line with recent biomarker development, which combined pro and anti-inflammatory markers to improve prediction of deleterious outcomes such as secondary infections ( 45 , 46 ). This was, for example, described in trauma patients with the association of plasma IL-6 levels and mHLA-DR ( 47 ).…”
Section: Discussionsupporting
confidence: 84%
“…These results are in line with recent biomarker development, which combined pro and anti-inflammatory markers to improve prediction of deleterious outcomes such as secondary infections ( 45 , 46 ). This was, for example, described in trauma patients with the association of plasma IL-6 levels and mHLA-DR ( 47 ).…”
Section: Discussionsupporting
confidence: 84%
“…In addition, this threshold is currently used in ongoing trials (NCT02361528 and NCT04990232). Notably, recent observational studies ( 21 , 22 ) also reported on this threshold to define groups of patients at increased risk of deleterious outcomes and similarly used 8,000 AB/C as a threshold for identifying immunosuppression. That said, next prospective investigations may focus on a more continuous adjustment of the IPP algorithm according to various levels of immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…This was a multicenter prospective cohort analysis (ClinicalTrials.gov Identifier: NCT03058211) (accessed on 1 July 2021) [11]. The baseline characteristics, clinical outcomes, and prognostic factors related to myocardial damage were assessed.…”
Section: Methodsmentioning
confidence: 99%